PENERAPAN TERAPI BEKAM BASAH DENGAN KELUHAN NYERI TENGKUK LEHER PADA PASIEN HIPERTENSI DI RUMAH SEHAT ZEIN HOLISTIK THERAPY MAKASSAR - A Nurul Nisa; Sunarti; Mardiah; Samsualam (Jurnal Kesehatan, 2025)
Hypertension is one of the non-communicable diseases that has a high prevalence and is the main risk factor for cardiovascular complications. One of the complaints that often arise in hypertensive patients is neck pain due to increased blood pressure and muscle tension. Wet cupping therapy is one of the complementary treatment methods that has been proven to be able to lower blood pressure while reducing pain complaints by removing blood containing pathological substances from the body. This study used a case study method on a patient (Mrs. D) with complaints of neck pain and hypertension at Rumah Sehat Zein Holistik Therapy Makassar. The nursing care process is carried out through the stages of review, determination of nursing diagnosis, intervention, implementation, and evaluation. Wet cupping therapy is given at specific points related to complaints of neck pain and hypertension. The results showed a decrease in pain intensity from a scale of 4 (moderate pain) to a milder scale after the intervention, accompanied by improved comfort and a decrease in patient blood pressure. The overall evaluation showed that wet cupping therapy was able to provide a relaxing effect, reduce complaints of neck pain, and help control blood pressure in hypertensive patients. Conclusions: Wet cupping therapy is effectively used as a complementary therapy to reduce neck pain while helping to control blood pressure in hypertensive patients. These results are expected to be considered in holistic nursing practice, especially in non-pharmacological management in hypertensive patients.